Dinamika Komunikasi Lintas Agama Islam dan Hindu di Jogja TV - Syafi’i, Muhammad Imam; Rahmatika, Arina (Universitas Islam Negeri Raden Intan Lampung, 2024)
Interfaith communication is important in every aspect of people's lives, including in the scope of the company where someone works which has employees with different religions. Jogja TV is one of the television station companies in Yogyakarta which has employees with different backgrounds and religions. There are 4 religions embraced by Jogja TV employees, namely Islam, Christianity, Catholicism and Hinduism. However, this research is more focused on discussing the dynamics of communication that exist between Muslim and Hindu employees at Jogja TV, as well as what factors support and hinder the communication process. The aim of this research is to find out the dynamics and what are the supporting and inhibiting factors in the communication process between Islamic and Hindu religions on Jogja TV. This research method is descriptive with a qualitative approach, with data collection techniques carried out by observation, interviews with Jogja TV employees and documentation, then data analysis is carried out by reducing the data, presenting the data and then drawing conclusions. The communication established by Jogja TV employees from its inception until now has experienced developments in terms of tolerance and moderation in matters of religion because these differences make interactions more harmonious. In the process of communication between Islamic and Hindu religions on Jogja TV, there are 2 supporting factors, namely the need to interact with other people and work, then differences of opinion often become obstacles in the communication process between Islamic and Hindu religions on Jogja TV.